2000
DOI: 10.1007/s150100070031
|View full text |Cite
|
Sign up to set email alerts
|

Tale of a Toothpick: Eikenella corrodens Osteomyelitis

Abstract: Tale of a Toothpick is a case of Eikenella corrodens osteomyelitis in a young woman, that resulted from puncture of her foot with a toothpick. The epidemiology, microbiology, common clinical presentations and therapy of E. corrodens are reviewed. A brief summary of the extent of toothpick injuries and their infectious complications are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…2 One of the concerns with infection by E. corrodens is that it is isolated not only from periodontal pockets, but also in systemic infections such as bite wounds, osteomyelitis, etc. [3][4][5][6][7] Several studies suggested that E. corrodens was associated with juvenile periodontitis [8][9][10] or active sites in periodontal pockets. 11,12 On the other hand, a study by Socransky et al showed a weak association with adult periodontitis.…”
mentioning
confidence: 99%
“…2 One of the concerns with infection by E. corrodens is that it is isolated not only from periodontal pockets, but also in systemic infections such as bite wounds, osteomyelitis, etc. [3][4][5][6][7] Several studies suggested that E. corrodens was associated with juvenile periodontitis [8][9][10] or active sites in periodontal pockets. 11,12 On the other hand, a study by Socransky et al showed a weak association with adult periodontitis.…”
mentioning
confidence: 99%
“…Agarwal found that more than 80% of patients with retained foreign bodies were boys and 58% involved the foot 5 . Other authors have noted that children and adolescents are prone to toothpickrelated injuries, particularly involving the foot 3,[6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides endocarditis, E. corrodens is mostly isolated from soft-tissue infections. Rare cases of osteomyelitis were associated with direct [7] or indirect inoculation of saliva like betel quid chewing [8], fingernail biting [9], human bite [10], toothpick injuries [11], fist-fighting injuries [12], and "needle licker's injuries" in IVDU [13,14].…”
Section: Discussionmentioning
confidence: 99%